2014
DOI: 10.19106/jmedscie004604201403
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum malondialdehyde levels and severity of acne vulgaris on male

Abstract: Acne vulgaris is a multifactorial disorder characterized by seborrhea, microcomedones, comedones, papules, pustules, nodules and possibly scarring. The pathogenesis of acne is not completely understood. Recent studies reported the possible role of reactive oxygen spesies (ROS) especially lipid peroxides in mediating acne inflammation. Malondialdehyde (MDA) is one of the final products of the lipid peroxidation that commonly used as a lipid peroxidation marker. This study was conducted to evaluate the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In addition, it has been reported that reactive oxygen derivatives released against microorganisms from neutrophils in the follicular wall contribute to the development of inflammation and are involved in the pathogenesis of the disease. [ 4 5 6 ] Oxidative stress is caused by the imbalance between the production of reactive oxygen/nitrogen derivatives and the antioxidant defense system and is involved in the pathogenesis of many diseases such as cardiovascular diseases, diabetes, cancer, and neurodegenerative diseases. Moreover, a growing body of evidence indicates that it also plays an important role in the pathogenesis of acne.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that reactive oxygen derivatives released against microorganisms from neutrophils in the follicular wall contribute to the development of inflammation and are involved in the pathogenesis of the disease. [ 4 5 6 ] Oxidative stress is caused by the imbalance between the production of reactive oxygen/nitrogen derivatives and the antioxidant defense system and is involved in the pathogenesis of many diseases such as cardiovascular diseases, diabetes, cancer, and neurodegenerative diseases. Moreover, a growing body of evidence indicates that it also plays an important role in the pathogenesis of acne.…”
Section: Introductionmentioning
confidence: 99%